If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1x = 3(x + 10) Reorder the terms: 6 + -1x = 3(10 + x) 6 + -1x = (10 * 3 + x * 3) 6 + -1x = (30 + 3x) Solving 6 + -1x = 30 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + -1x + -3x = 30 + 3x + -3x Combine like terms: -1x + -3x = -4x 6 + -4x = 30 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -4x = 30 + 0 6 + -4x = 30 Add '-6' to each side of the equation. 6 + -6 + -4x = 30 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = 30 + -6 -4x = 30 + -6 Combine like terms: 30 + -6 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 | | f(x)=6x^2+36x+192 | | x+37=129 | | 4+(m/5)=6 | | -5n-8-56m=-8 | | 4x^2+9=2x^2+3(5x+3) | | (2x^2)-(1x)-24=0 | | 12h^2-31h+20= | | 3(2x-5)=18 | | x^6+7x^3+64=0 | | 6x=6x-9 | | 3(m+3)-16= | | 36=13w-4w | | X+2=289 | | 10x=-4x+-7 | | -mn+7mp+10m=-2n-8 | | 3a^2+9a+30=0 | | 32=7k-3 | | 4n-6=2n-2n+2 | | X^2-10x-263=0 | | -(1+b)=-(3b-3) | | 2(9-4)+15=13 | | 2(50+-1.5y)+3y=100 | | 52-(2c+3)=4(3+7)+c |